The measurement of skin to epiglottis length for difficult airway prediction by ultrasonography in obese pregnant women: Prospective cohort study - Ünal Kantekin, Çiğdem; Erkoç, Mustafa Fatih; Talih, Gamze (Journal of Surgery and Medicine, 2019)
Aim: The risk of difficult airway is high in obstetric anesthesia, and weight gain above physiological limits further increases this risk. Ultrasonography (USG) has often been used recently in airway evaluation of all patient groups. The aim of this study was to investigate the effect of weight gain beyond physiological limits on the measurement of the distance of the skin-to epiglottis (DSE) with USG. Methods: 50 pregnant women aged between 20-40 years, half of which had gained weight within physiological limits during pregnancy (<15kg) (Group 1) and the other half whose weight gain was equal to or greater than 15 kilograms (Group 2) were included in this study. The measurements were labelled as “a” and “b” for the first and third trimesters. Mallampati evaluation was made during ultrasonographic measurements in all pregnant patients by an anesthesiologist blinded to the study. Results: No statistically significant difference was determined between the Group 1 and Group 2 pregnant patients with respect to age, BMI, and distance of skin to epiglottis (DSE) values (P=0.293, P=0.281, P=0.515). A statistically significant increase in BMI and DSE was detected in Group 2b when compared to Group 1b (both: P<0.001). Conclusion: Ultrasonographic DSE measurement in pregnant women with weight gain above the physiological limit during pregnancy may be used to predict difficult airways when utilized together with Mallampati scoring, especially during the third trimester.